2006
DOI: 10.1637/7528-032006r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Infectious Bursal Disease Viruses from Asymptomatic Broiler Flocks in Europe

Abstract: Infectious bursal disease virus (IBDV) exists in several different antigenic and pathogenic forms. The immune suppression caused by this virus in young chickens is not always associated with clinical signs of disease. The antigenic variant viruses originally described in the United States typically do not cause clinical signs of disease but can cause a marked immune suppression via the destruction of B lymphocytes. Using a reverse transcription-polymerase chain reaction (RT-PCR) assay we conducted a survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…This seems plausible, since Domanska et al (9) described sequences of IBDV strains present during the late 1970s and early 1980s in Europe containing a serine at position 222 and causing subclinical infectious bursal disease. Interestingly, Jackwood et al (14) recently reported the presence of new IBDV isolates in Europe with VP2 sequences distinct from those of previous European IBDV isolates (classical and very virulent) and Belg-IBDV. The sequences were highly related to an IBDV variant circulating in the United States.…”
Section: Discussionmentioning
confidence: 97%
“…This seems plausible, since Domanska et al (9) described sequences of IBDV strains present during the late 1970s and early 1980s in Europe containing a serine at position 222 and causing subclinical infectious bursal disease. Interestingly, Jackwood et al (14) recently reported the presence of new IBDV isolates in Europe with VP2 sequences distinct from those of previous European IBDV isolates (classical and very virulent) and Belg-IBDV. The sequences were highly related to an IBDV variant circulating in the United States.…”
Section: Discussionmentioning
confidence: 97%
“…This is necessary because it is possible that the analyzed viral sequences represent viral populations that are present in the bursal sample but are impeded because of a decreased ability to replicate in the host. Emergence and evolution of new antigenic variants has been documented since the mid-1980s in the United States (24,26) and, most recently, in Europe (7,14).…”
Section: Discussionmentioning
confidence: 99%
“…The virus infects and destroys actively dividing IgM-bearing B cells in the bursa of fabricius [2,3]. IBDV exists in different antigenic and pathogenic forms [4]. Initial isolates designated as classical strains (cIBDV) of the serotype 1 viruses were considered to be a single antigenic type.…”
Section: Introductionmentioning
confidence: 99%